Enhancing emotional resilience in pre-service early childhood educators through digital learning environments - Gulmira Mombiyeva; Ulbossyn Kyyakbayeva; Perizat Dautkaliyeva; Zhanna Zhunisbekova; Zhanar Saduova; Zhaxygul Issayeva (International Journal of Evaluation and Research in Education (IJERE), 2026)
Emotional resilience (ER) is a critical competence for pre-service teachers, enabling them to manage stress, adapt to change, and maintain professional functioning. Digital learning (DL) environments present both challenges and opportunities for developing ER, yet empirical studies on structured interventions in these contexts remain limited, particularly in early childhood education (ECE). This study examined the effect of a structured DL intervention on the development of ER among pre-service teachers in ECE contexts in Kazakhstan. A quasi-experimental pretest-posttest design with non-equivalent groups was employed, involving 165 female pre-service teachers. The intervention included scaffolded digital tasks, reflective exercises, and instructor-led feedback. Baseline ER scores were comparable between groups. Following the intervention, participants in the experimental group (EG) demonstrated significantly higher ER compared to those in the control group (CG). These results indicate that structured DL interventions can effectively enhance ER by fostering adaptive coping, self-regulation, and problem-solving skills. Embedding scaffolded digital tasks combined with reflection and feedback into teacher education programs may support the preparation of resilient, reflective, and emotionally competent educators.